2020
DOI: 10.3389/fpsyt.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Interoception in Anorexia Nervosa: Exploring Associations With Alexithymia and Autistic Traits

Abstract: Background: Previous research on whether interoception is altered in anorexia nervosa (AN) using the heartbeat tracking task has yielded inconsistent results. However, no previous research has examined whether interoception is associated with alexithymia and autistic traits in AN, conditions which are more prevalent in this population and thought to be related to performance in this task. The aim of this study was to explore whether altered interoception in AN is associated with alexithymia and autistic traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Similar results have been observed when considering self-reported attention across interoceptive domains in both adolescents and adults (Brown et al, 2017). Pollatos et al (2008) reported impaired perception of cardiac signals in AN patients; however, several studies have failed to replicate this result (Eshkevari et al, 2014;Kinnaird et al, 2020;Lutz et al, 2019). Kinnaird et al (2020) reported that AN patients believed their accuracy of perception to be impaired, and these beliefs correlated with illness severity.…”
Section: Empirical Research: Interoception In Eating Disorderssupporting
confidence: 68%
“…Similar results have been observed when considering self-reported attention across interoceptive domains in both adolescents and adults (Brown et al, 2017). Pollatos et al (2008) reported impaired perception of cardiac signals in AN patients; however, several studies have failed to replicate this result (Eshkevari et al, 2014;Kinnaird et al, 2020;Lutz et al, 2019). Kinnaird et al (2020) reported that AN patients believed their accuracy of perception to be impaired, and these beliefs correlated with illness severity.…”
Section: Empirical Research: Interoception In Eating Disorderssupporting
confidence: 68%
“…Atypical interoception is ubiquitous across psychiatric and neurological conditions. While certain conditions have long been associated with atypical interoception, such as Feeding and Eating Disorders (EDs) including anorexia Nervosa, Bulimia Nervosa, and obesity ( Eshkevari et al, 2014 ; Fassino et al, 2004 ; Kinnaird et al, 2020 ; Klabunde et al, 2013 ; Lapidus et al, 2020 ; Lattimore et al, 2017 ; Lutz et al, 2019 ; Pollatos et al, 2008 ; although see e.g. Ambrosecchia et al, 2017 ; Kinnaird et al, 2020 ), the full range of conditions impacted by interoceptive atypicalities is only just being realised ( Barrett and Simmons, 2015 ; Brewer et al, 2016a ; Brewer, HappĂ©, et al, 2015 ).…”
Section: Increased Prevalence Of Interoceptive Impairments In Clinical Conditionsmentioning
confidence: 99%
“…While certain conditions have long been associated with atypical interoception, such as Feeding and Eating Disorders (EDs) including anorexia Nervosa, Bulimia Nervosa, and obesity ( Eshkevari et al, 2014 ; Fassino et al, 2004 ; Kinnaird et al, 2020 ; Klabunde et al, 2013 ; Lapidus et al, 2020 ; Lattimore et al, 2017 ; Lutz et al, 2019 ; Pollatos et al, 2008 ; although see e.g. Ambrosecchia et al, 2017 ; Kinnaird et al, 2020 ), the full range of conditions impacted by interoceptive atypicalities is only just being realised ( Barrett and Simmons, 2015 ; Brewer et al, 2016a ; Brewer, HappĂ©, et al, 2015 ). There is evidence of increased prevalence of atypical interoception in anxiety and panic disorders ( Ehlers and Breuer, 1992 ; Paulus and Stein, 2010 ; AdriĂĄn Yoris et al, 2015 ), alcohol and substance abuse ( Jakubczyk et al, 2019 ; Naqvi and Bechara, 2010 ; Paulus and Stewart, 2014 ; Paulus et al, 2009 ; Verdejo-Garcia et al, 2012 ), depression ( Aaronson et al, 2017 ; Dunn et al, 2007 ; Furman et al, 2013 ; Harshaw, 2015 ; Paulus and Stein, 2010 ; Pollatos et al, 2009 ), somatoform disorders ( Schaefer et al, 2012 ), Autism Spectrum Disorder (ASD; Garfinkel et al, 2016a ; Hatfield et al, 2017 ; Mul et al, 2018 ; Nicholson et al, 2019 ), Attention-Deficit/Hyperactivity Disorder (ADHD; Kutscheidt et al, 2019 ), Obsessive Compulsive Disorder (OCD; Lazarov et al, 2010 ; Schultchen et al, 2019 ; see also Stern, 2014 for a discussion), schizophrenia ( Ardizzi et al, 2016 ), depersonalisation/derealisation disorder ( Schulz et al, 2015 ; Sedeño et al, 2014 ; but see Michal et al, 2014 ), personality disorders ( Mussgay et al, 1999 ; although see Hart et al, 2013 ), and those with high levels of psychopathic traits ( Nen...…”
Section: Increased Prevalence Of Interoceptive Impairments In Clinical Conditionsmentioning
confidence: 99%
“…We also include a confidence measure to investigate whether between-group differences in estimation confidence could be found-in line with recent proposals regarding eating disorders and confidence in bodily perception and belief (Fassino et al, 2004;Jenkinson et al, 2018;Kinnaird et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Other research focuses on the confidence patients exhibit in their perception of their own bodily states. These results suggest that patients exhibit low confidence in their perception of interoceptive sensations such as hunger and heartbeat (Fassino et al, 2004;Jenkinson et al, 2018;Kinnaird et al, 2020).…”
Section: Introductionmentioning
confidence: 95%